1987
DOI: 10.1111/j.1432-1033.1987.tb13630.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of signal transfer from beta1-adrenoceptor to adenylate cyclase by betagamma subunits in a reconstituted system

Abstract: The By subunits of guanine nucleotide binding proteins from bovine brain and bovine rod outer segments have different structural and immunochemical properties. In spite of these structural differences, py subunits from these sources have been found to be fully interchangeable in terms of their interaction with a subunits of pertussistoxin-sensitive G proteins. In contrast, however, there are striking differences between these by subunits with regard to their ability to deactivate fluoride-stimulated G,. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 58 publications
(36 reference statements)
3
20
0
Order By: Relevance
“…Absorbance and protein determinations indicated that FITC was coupled to the purified B1-adrenoceptor in a molar ratio of approximately 1: 1. The ability of the fluorescent B-adrenoceptor to activate G, in the presence of I(-)isoproterenol and GTP[yS] was tested as described before [15] and was found to be like that of an unlabelled receptor preparation [18 b] (and Frohlich et al, unpublished results). The purity of the receptor preparation is shown in Fig.…”
Section: Preparation O F B 1 -Adrenoceptormentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbance and protein determinations indicated that FITC was coupled to the purified B1-adrenoceptor in a molar ratio of approximately 1: 1. The ability of the fluorescent B-adrenoceptor to activate G, in the presence of I(-)isoproterenol and GTP[yS] was tested as described before [15] and was found to be like that of an unlabelled receptor preparation [18 b] (and Frohlich et al, unpublished results). The purity of the receptor preparation is shown in Fig.…”
Section: Preparation O F B 1 -Adrenoceptormentioning
confidence: 99%
“…GTPase activity was determined as described in [15]. Purified G-proteins in vesicles or in 0.1% Lubrol PX solution were incubated in 50 mM Hepes, 0.1 mM EDTA-Na2, 1 mM dithiothreitol and 0.2 mM MgC12 pH 7.8, with 1 pM [y-32P]GTP (3-6 cpm/fmol) for 20 min at 30°C.…”
Section: G Tpase Assaymentioning
confidence: 99%
“…Moreover, the fly-complex alone attaches to the receptor (Im et al, 1988;Kurstjens et al, 1991) and appears to be part of the recognition site for G-protein -a-subunits. by-Subunits also contribute in a concentration-dependent manner both to the hormonal activation and to the deactivation of G,, (Hekman et al, 1987).…”
Section: Structural Properties Of G-proteinsmentioning
confidence: 99%
“…They are interchangeable among the a-subunits of the nonretinal G-proteins, G,, Gi, Go, but G,, can discriminate between transducin fly, and the fly complex resolved from the nonretinal G-proteins of the brain (Hekman et al, 1987;Casey et al, 1989). However, quantitative information is lacking.…”
Section: Structural Properties Of G-proteinsmentioning
confidence: 99%
“…Moreover, when &-subunits purified from bovine brain were added to purified 0-adrenoceptor in lipid vesicles in the presence of G, also purified from turkey erythrocytes, the fly-subunits promoted the interaction of the /3-adrenoceptor with G, and increased its GTPase activity (Hekman et al, 1987). These observations became the starting point of a new line of research that I have followed ever since.…”
mentioning
confidence: 99%